Development and validation of a one-dimensional simulation model of a hermetic reciprocating compressor for household refrigeration. (2nd February 2010) - Abidin, Zainal; Lang, Wolfgang; Almbauer, Raimund A.; Nagy, Daniel; , Adolf Burgstaller
In a hermetic reciprocating compressor (HRC), all components inside the shell interact thermally with each other, and thus all components inside the shell must be taken into account to get a complete thermodynamic analysis of a HRC. A one-dimensional simulation provides useful results as long as the thermal boundary conditions are well known. In this work, a procedure for the development and the validation of a one-dimensional simulation model of a HRC is elaborated. A thermal network (TNW) is added to the one-dimensional simulation model to obtain the thermal boundary conditions. A zero-dimensional model is applied for the calculation of the gas inside the plenums, the junctions and the cylinder. Five experimental test cases are proposed to check the validation and the consistency of the model. Finally, the procedure is applied for a 5.6 ccm hermetic compressor for isobutane.